2007
DOI: 10.1007/s00382-006-0219-4
|View full text |Cite
|
Sign up to set email alerts
|

Source of low frequency modulation of ENSO amplitude in a CGCM

Abstract: We study the relationship between changes in equatorial stratification and low frequency El Niñ o/ Southern Oscillation (ENSO) amplitude modulation in a coupled general circulation model (CGCM) that uses an anomaly coupling strategy to prevent climate drifts in the mean state. The stratification is intensified at upper levels in the western and central equatorial Pacific during periods of high ENSO amplitude. Furthermore, changes in equatorial stratification are connected with subsurface temperature anomalies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…8 Hence, it is to be expected that very low frequency changes in the mean state will affect the statistics and spatial structure of ENSO (e.g., Fedorov and Philander 2000). Moon et al (2007) argued that the low-frequency modulation of ENSO variance in the Center for Ocean-Land-Atmosphere (COLA) climate model was due to low-frequency changes in the stratification of the near-equatorial ocean that stemmed from wind stress forcing in the subtropical southern Pacific Ocean. Matei et al (2008) demonstrated that SST anomalies placed in the southern subtropical Pacific of the ECHAM5-Max Planck Institute Ocean Model (MPI-OM) coupled model eventually make their way to the equator and cause mean state changes that affect the variance in ENSO.…”
Section: Statementioning
confidence: 99%
“…8 Hence, it is to be expected that very low frequency changes in the mean state will affect the statistics and spatial structure of ENSO (e.g., Fedorov and Philander 2000). Moon et al (2007) argued that the low-frequency modulation of ENSO variance in the Center for Ocean-Land-Atmosphere (COLA) climate model was due to low-frequency changes in the stratification of the near-equatorial ocean that stemmed from wind stress forcing in the subtropical southern Pacific Ocean. Matei et al (2008) demonstrated that SST anomalies placed in the southern subtropical Pacific of the ECHAM5-Max Planck Institute Ocean Model (MPI-OM) coupled model eventually make their way to the equator and cause mean state changes that affect the variance in ENSO.…”
Section: Statementioning
confidence: 99%
“…ENSO modulation may be partly intrinsic, arising from chaotic and/or stochastically driven tropical Pacific dynamics (Kleeman and Power 1994;Blanke et al 1997;Timmermann et al 2003;Jochum and Murtugudde 2004;Fl€ ugel et al 2004;Yeh et al 2004;Power and Colman 2006;Vecchi et al 2006b;Gebbie et al 2007;Zavala-Garay et al 2008;Wittenberg 2009;Newman et al 2011a,b). ENSO may also be modulated by slow changes in background climate, arising from ENSO nonlinearities, non-ENSO climate modes, or natural and anthropogenic radiative forcings (Kirtman and Schopf 1998;Wang andAn 2001, 2002;Wittenberg 2002;Zhang and DeWitt 2006;Moon et al 2007;An et al 2008;Matei et al 2008;Anderson et al 2009;Imada and Kimoto 2009;DiNezio et al 2012;Ogata et al 2013). These mechanisms are compatible, and indeed existing observational records are not yet sufficient to rule out the possibility of a stochastically driven, chaotic ENSO perturbed by both non-ENSO climate modes and external forcings (Chang et al 1996;Penland et al 2000;Zhang et al 2003;Fedorov et al 2003;Fl€ ugel et al 2004;Kravtsov 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We attempt to address such limitations in this study and further improve the lead time of ENSO prediction. Moreover, ENSO shows strong physical linkages with the slowly evolving oceanic components in the tropical Pacific (Chen et al, 2004;Moon et al, 2007;Luo et al, 2008;Ramesh and Murtugudde, 2012;Ogata et al, 2013;Zhao et al, 2021), Indian Ocean (Behera et al, 2006;Izumo et al, 2010;Luo et al, 2010;Kug and Kang, 2006), Atlantic Ocean (Ham et al, 2013(Ham et al, , 2021aChikamoto et al, 2020;Richter and Tokinaga, 2020), western hemisphere warm pool (Park et al, 2018), and North Pacific regions (Larson and Kirtman, 2014;Pegion and Selman, 2017;Tseng et al, 2017) at longer lead times. They can work as potential sources of the long lead predictability of ENSO.…”
Section: Introductionmentioning
confidence: 99%